Lignin-Based Nanoparticles as Both Structural and Active Elements in Self-Assembling and Self-Healing Multifunctional Hydrogels for Chronic Wound Management - A. Gala Morena; Sílvia Pérez-Rafael; Tzanko Tzanov (MDPI AG, 2022)
Efficient wound healing is feasible when the dressing materials simultaneously target multiple factors causing wound chronicity, such as deleterious proteolytic and oxidative enzymes and bacterial infection. Herein, entirely bio-based multifunctional self-assembled hydrogels for wound healing were developed by simply mixing two biopolymers, thiolated hyaluronic acid (HA-SH) and silk fibroin (SF), with lignin-based nanoparticles (NPs) as both structural and functional elements. Sono-enzymatic lignin modification with natural phenolic compounds results in antibacterial and antioxidant phenolated lignin nanoparticles (PLN) capable of establishing multiple interactions with both polymers. These strong and dynamic polymer-NP interactions endow the hydrogels with self-healing and shear-thinning properties, and pH-responsive NP release is triggered at neutral to alkaline pH (7-9). Despite being a physically crosslinked hydrogel, the material was stable for at least 7 days, and its mechanical and functional properties can be tuned depending on the polymer and NP concentration. Furthermore, human skin cells in contact with the nanocomposite hydrogels for 7 days showed more than 93% viability, while the viability of clinically relevant Staphylococcus aureus and Pseudomonas aeruginosa was reduced by 99.7 and 99.0%, respectively. The hydrogels inhibited up to 52% of the activity of myeloperoxidase and matrix metalloproteinases, responsible for wound chronicity, and showed a strong antioxidant effect, which are crucial features promoting wound healing.